The Effectiveness of the Sustainability Balanced Scorecard A Sustainable Business Performance Measurement Tool - Nur Fadilah Hanifah; Edo Arta Fandala Putra; Mukhtaruddin Mukhtaruddin (Dinasti Publisher, 2025)
This study focuses on the sustainability balanced scorecard (SBSC) as a performance measurement and management control tool that can play a significant role in driving companies towards sustainability goals. According to previous studies, research on SBSC can be structured into design, implementation, use, and evolution stages. This study aims to systematize knowledge at the use stage. Specifically, the study discusses the determinants influencing SBSC use, the approaches companies use in SBSC application, and the resulting results in terms of their effects on sustainability control and management. The method used is a systematic literature review (SLR) of 100 journal articles published in Scopus-indexed journals (Q1–Q4) and Sinta 2 to Sinta 4 within the period 2016–2025. The findings add to the body of literature on SBSC in management and accounting, provide an overview of current research, map research streams, suggest potential future research paths, and highlight several managerial implications.